PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK DENGAN INSENTIF PAJAK SEBAGAI PEMODERASI (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI) - Hidayat, Kholid; Ompusunggu, Arles P.; H. Suratno, H. Suratno (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2016)
This study is aimed to examine the effect of Corporate Social Responsibility (CSR) to tax aggresiveness with tax incentive as a moderator. The study population used was the mining companies listed in Indonesia Stock Exchange with sample consisted of 34 companies which were obtained by purposive sampling method between 2011 and 2015. This study used CSR (as independent variable), tax aggressiveness (as dependent variable) and tax incentive (as moderating variable). To control the effect of CSR to tax aggressiveness, this study used variable controls namely leverage, size, Return On Assets (ROA), capital intensity and inventory intensity. While dependent variable, tax aggressiveness, was measured by using a proxy: Effective Tax Rate (ETR). CSR has been carried out by using Corporate Social Responsibility Index (CSRI) and data analysis technique has been done by using Moderated Regression Analysis (MRA). In addition the data was processed by using SPSS 22. The result showed that CSR has negative influence to tax agressiveness. The higher the level of corporationâs CSR disclosure, the lower is the level of tax aggressiveness.Tax incentives was proven and capable to strenghthen the relation between CSR and tax aggressivenes. CSR simultantly tested with the control variables showed similar result. It has negative influence.The higher the level of corporationâs CSR disclosure, the lower is the level of tax aggressiveness.Â Keywords: CSR, Tax Aggressivenes, Tax Incentives